(untitled) (Research, Society and Development, 2022)
Objective: To analyze the association between venous thromboembolism and the use of oral contraceptives. Methodology: This is an integrative review. A bibliographic survey was conducted in the databases at the Virtual Health Library (VHL) and PUBMED, in Portuguese and English. The information extracted from the selected articles was referred to the following items: journal and article title; authors’ titration; year, location, volume and publication number. In addition to these items, in the studies we observed information about the methodologies used, the results achieved and the conclusions to which the authors reached. Results: A total of 8 articles were found and after a refinement mechanism in the search on the platforms by the inclusion criteria, 7 papers were included, because one was outside the selected language. These were subject to a deep analysis and observed if the subject addressed is consistent with the recommendations of the present study, obeying the exclusion criteria. Conclusion: Based on the results obtained in the present study, it is observed that the high risk of DVT or PE are in patients who use combined contraceptives. Findings in the literature have not yet understood which oral contraceptive is more harmful to women’s health, however, it is noted that the association of drospirinone and third-generation progestágens or the fourth generation combined oral contraceptive has a slightly higher risk of VTE when compared to patients who use first and second generation.